Facile synthesis of 1-alkoxy-1H-benzo- and 7-azabenzotriazoles from peptide coupling agents, mechanistic studies, and synthetic applications - Lakshman, Mahesh K.; Singh, Manish K.; Kumar, Mukesh; Chamala, Raghu Ram; Yedulla, Vijayender R.; Wagner, Domenick; Leung, Evan; Yang, Lijia; Matin, Asha; Ahmad, Sadia (Beilstein Journal of Organic Chemistry, 2014)
(1H-Benzo[d][1,2,3]triazol-1-yloxy)tris(dimethylamino)phosphonium hexafluorophosphate (BOP), 1H-benzo[d][1,2,3]triazol-1-yl 4-methylbenzenesulfonate (Bt-OTs), and 3H-[1,2,3]triazolo[4,5-b]pyridine-3-yl 4-methylbenzenesulfonate (At-OTs) are classically utilized in peptide synthesis for amide-bond formation. However, a previously undescribed reaction of these compounds with alcohols in the presence of a base, leads to 1-alkoxy-1H-benzo- (Bt-OR) and 7-azabenzotriazoles (At-OR). Although BOP undergoes reactions with alcohols to furnish 1-alkoxy-1H-benzotriazoles, Bt-OTs proved to be superior. Both, primary and secondary alcohols undergo reaction under generally mild reaction conditions. Correspondingly, 1-alkoxy-1H-7-azabenzotriazoles were synthesized from At-OTs. Mechanistically, there are three pathways by which these peptide-coupling agents can react with alcohols. From 31P{1H}, [18O]-labeling, and other chemical experiments, phosphonium and tosylate derivatives of alcohols seem to be intermediates. These then react with BtO− and AtO− produced in situ. In order to demonstrate broader utility, this novel reaction has been used to prepare a series of acyclic nucleoside-like compounds. Because BtO− is a nucleofuge, several Bt-OCH2Ar substrates have been evaluated in nucleophilic substitution reactions. Finally, the possible formation of Pd π–allyl complexes by departure of BtO− has been queried. Thus, alpha-allylation of three cyclic ketones was evaluated with 1-(cinnamyloxy)-1H-benzo[d][1,2,3]triazole, via in situ formation of pyrrolidine enamines and Pd catalysis.
Keywords: alkoxy; azabenzotriazole; benzotriazole; peptide-coupling; phosphonium